El sistema sexo-género en los movimientos feministas - Teresa Aguilar García (Amnis)
In this text the theoretical pair sex/gender is analyzed from its birth, according to the first researching on sexual dimorphism at the beginning of the 20th century, that showed how gender was socially determinate, whereas sex was determinate genetically. Also one analyzes the paper that this theoretical pair has played within the French Feminism of the Différence, the Radical Feminism and the Queer Movement. The analysis approach is from the materialistic feminist Haraway, who maintains in its fundamental work: Science, Cyborgs and Women. The Reinvention of Nature, a position that rejects the division sex/gender, to consider that it has lead terrible consequences in the feminism’s history. On the other hand, the article also starts from the constructivism of Butler and the performative theory of gender, as well as discusses the paper of drag-queen like subversive agent who could oppose the imposed heterosexual code, or of the queer movement like destabilizing agent of the capitalist system, confronted with Rodriguez Magda, who introduces the concept of simulacrum of Baudrillard to explain the paper of drag-queen.